2022
DOI: 10.1007/s00420-022-01908-x
|View full text |Cite
|
Sign up to set email alerts
|

Health and related behaviours of fly-in fly-out workers in the mining industry in Australia: a cross-sectional study

Abstract: Background Fly-In Fly-Out (FIFO), which entails travelling mostly from the urban areas to stay and work in remote areas for designated periods and travel back home to spend designated days of leave, has become a common work arrangement in the mining sector globally. This study examined the mental and physical health of FIFO workers and described their health-related behaviours during on-and off-shift periods. Methods A cross-sectional study was conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…Figure 1 outlines the flow of participants into the present study. Of the 216 workers that completed the cross‐sectional study (Asare, Robinson, Powell, et al., 2022), 52 (24.1%) agreed to take part in the present study. Of the 52 participants included in the study, 8 (15.4%) could not be reached to schedule the daily surveys, and 21 (%) did not respond to at least three daily diaries in both the on‐shift and off‐shift phases, which was set as a minimum threshold for data provision for statistical modelling (Figure 1).…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…Figure 1 outlines the flow of participants into the present study. Of the 216 workers that completed the cross‐sectional study (Asare, Robinson, Powell, et al., 2022), 52 (24.1%) agreed to take part in the present study. Of the 52 participants included in the study, 8 (15.4%) could not be reached to schedule the daily surveys, and 21 (%) did not respond to at least three daily diaries in both the on‐shift and off‐shift phases, which was set as a minimum threshold for data provision for statistical modelling (Figure 1).…”
Section: Methodsmentioning
confidence: 93%
“…This is the first study to examine affects during on‐and off‐shift periods. Several cross‐sectional studies have indicated high levels of psychological distress among FIFO workers (e.g., Asare et al., 2021; Asare, Robinson, Powell, et al., 2022). FIFO workers, during work periods, are separated from their families and faced with the emotional strain of dealing with being away from families, loneliness and social isolation, anxiety about maintaining family and social relationships and missing important family events (Gardner et al., 2018; Torkington et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many workers spend their week off between swings resting, hence the return to work which involves adapting to an early-wake up sleep routine and the general workplace environment at the start of a swing may have negatively affected initial processing efficiency. Asare et al (2022) conducted a survey of 216 Australian FIFO workers and reported that total sleep time on site was significantly less compared to when at home. If sleep time or attention increased over the course of the swing then this may be a reason for improved speed in respect to recall and counting latency.…”
Section: Discussionmentioning
confidence: 99%